Organisational model of a globally oriented wood industry company - Kropivšek, Jože (Zbornik gozdarstva in lesarstva, 2007)
The paper provides an answer to the question as to in what way and with which organizational steps a wood industry company can be (more) adaptable and successful in a rapidly changing (global) business environment. The purpose ofthe article is to form an organizational model of a globally oriented wood industry company, considering the three required model properties: repeatability, efficiency and productiveness, as well as practical applicability. Research is limited to actual state in Slovenian wood industry practice with some specifics that should be considered by other implications of the research. Practical applicability of the model is based on these findings and is ensured by making guidelines on the basis of which companies can organise their businesses. These guidelines include suggested measures forindividual areas of business organization with the intention of increasing adaptability and innovativeness of business operation, improving competitive ability, and the ability of constant improvement. The paper provides a new organizational approach, specialized for making wood industry companies successful in the changing business environment.
Keywords: globalizacija; lesna industrija; modeli; organizacija poslovanja; podjetje; prilagodljivost